Grandma, could this dissertation be my Indigenous Tayal facial tattoo? An autoethnography of overcoming the fear of statistics through the dichotomous use of p-values - Lin, Hsiao-Ching, author; Most, David, advisor; Aragon, Antonette, advisor; Doe, Sue, committee member; Faircloth, Susan, committee member; Timpson, William, committee member (Colorado State University. Libraries, 2021)
This dissertation's idea began with my class notes and questions in the statistics courses I attended in my doctoral program. These notes and questions originally were about the concepts of the bell shape, statistical distribution, and hypothesis testing. They then became my inquiries of p-values because what I learned in the courses about how the dominant use of p-values have generated inequities such as academic bias and misleading statistics education; they caught my attention as inequities were at the root of my learning growing up as a Taiwanese Indigenous student and woman. I reference Indigenous critical theories' (ICT) concept of challenging the mastery of knowledge via centering Indigenous intelligence in the knowledge (Justice, 2016) as the primary epistemology to conduct this autoethnographic study. All in all, using autoethnography as the research method, I ask four research questions to explore my meaning-making of learning the dichotomous use of p-values: 1. How do I make meaning of the dichotomous use of p-values in the statistics courses I attended? The exploration of this research question illustrates how and why I was drawn to the issue of p-values and what is the essential problem of using p-values dichotomously. Using p-values dichotomously means using statistical significance to decide the effectiveness of a research treatment or intervention. 2. How do I make meaning of the dichotomous use of p-values in the literature of this study? The analysis of this research question shows the broader contexts of the canonical teaching and use of p-values and that of inequities engendered by them. To answer this research question, I explored the history and philosophy of the connection between statistics and scientific research and inequities caused by using p-values dichotomously. These inequities explored and explained in this study are death, job loss, life threats, and academic bias. 3. How do research questions 1 and 2 help me address inequities discussed in this study as an Indigenous woman researcher? The answer to this research question explains how the inequities generated from improper use of p-values. It also aligns with the inequities I have encountered as an Indigenous woman and graduate student in a country not of my birth. 4. How do research questions 1, 2, and 3 help me overcome my fear of statistics? Pondering this question led me to complete this dissertation—Grandma, Could This Dissertation Be My Indigenous Tayal Facial Tattoo? An Autoethnography of Overcoming the Fear of Statistics Through the Dichotomous Use of P-Values. This study not only critiques the dichotomous use of p-values but also explains the inequities generated from it by unraveling the social norm ingrained in the use of p-values. It also heals me from feeling unintelligent, timid, and small about statistics as, during the process of completing this dissertation, I have overcome the fear that accompanies emotional trauma associated with the numeric dimension of confirming realities.
Keywords: inequity; p-values; Indigenous women; graduate students; learning; academic bias; statistics; scientific research